Золушка: [для младшего школьного возраста] / Шарль Перро - Перро Шарль (Любимые книги детства, 2013)
Экземпляры: Ф.8 (20190904) / Инвентарный номер: 46494 / Цена: 50.00 / Авт.знак: П 27 / ГРНТИ: 17.82.93 / ББК: 84(4Фра)